International cooperation at a crossroads : aid, trade and security in an unequal world - United Nations Development Programme; Denny, Charlotte (New York : Published [for] United Nations Development Programme, 2005)
This report makes clear, the single greatest challenge facing the development community, and arguably the world is the challenge of meeting the Millennium Development Goals by the target date of 2015.
Includes notes and bibliographic notes.
Includes bibliographical references: p. 188-207.
ne 11/06/2021
Ref
Keywords: Economic development; Security, International; International trade; Peace; Economic assistance